Negative Impact of Pseudomonas aeruginosa Y12 on Its Host Musca domestica - Zhang, Qian; Wang, Shumin; Zhang, Xinyu; Zhang, Ruiling; Zhang, Zhong (Frontiers in Microbiology, 2021)
The gut microbiota is involved in multiple interactions affecting host insect health and plays an important role in the development of insect larvae. Entomopathogenic fungal infection can result in disorder of the gut microbiota and accelerate insect death. High concentrations of Pseudomonas aeruginosa significantly inhibit the development of housefly larvae, while low concentrations of P. aeruginosa exhibit little impact on the larvae. However, the pathogenic mechanism of P. aeruginosa towards housefly larvae remains unclear. In this study, the dynamic distribution of the gut microbiota of housefly larvae fed different concentrations of P. aeruginosa Y12 was investigated. Compared with low-concentration P. aeruginosa diets, orally administered high-concentration P. aeruginosa diets caused higher mortality and had a greater impact on the community structure and interaction network of intestinal flora in housefly larvae. The bacterial community of the gut microbiota in housefly larvae was reconstructed in 4 days. Bacterial abundance and diversity were significantly reduced in housefly larvae fed high concentrations of P. aeruginosa. A total of 10 cultivable bacterial species belonging to 9 genera were isolated from the intestine of housefly larvae among which Enterobacter hormaechei, Klebsiella pneumoniae, Enterobacter cloacae, Lysinibacillus fusiformis, and Bacillus safensis promoted the growth of larvae through feeding experiments. This study is the first to analyse the influence of high concentrations of P. aeruginosa on the gut microbiota of houseflies. Our study provides a basis for exploring the pathogenic mechanism of high concentrations of P. aeruginosa in houseflies.